PENGARUH PERTUMBUHAN PERUSAHAAN DAN LIKUIDITAS TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Musmahendra, Musmahendra (Universitas Ichsan Sidenreng Rappang, 2023)
In order to ascertain and investigate the impact of firm growth and liquidity on bond ratings of Go Public banking companies listed on the Indonesia Stock Exchange (IDX), this study will look at both variables. The research method is descriptive and employs a quantitative methodology. During the observation period from 2020 to 2021, samples were drawn using purposive sampling from 30 Go Public banking organizations. Logistic regression was used to evaluate this research methodology. According to the study's findings, the level of bonds is not significantly impacted by the company's growth. Liquidity also has no discernible impact on bond rates. A company's solid financial position will be indicated by high liquidity, which might impact bond ratings. The company's growth is the main factor that affects the bond grade. This is because a bond issuer will have an investment grade bond rating if the company's growth is deemed good, but not if it is not.